THE RECOMMENDATION OF SPACE LAY OUT ON CHILDREN AUTIS SCHOOL IN SURAKARTA - Musyawaroh Sugito; Edi Pramono Singgih; Sumaryoto Sumaryoto; Tri Joko Daryanto (ARSITEKTURA, 2018)
The number of autism sufferers worldwide is increasing, but not yet followed by optimal handling. The cost of autism therapy is unaffordable by the general public because of the need for a specific and expensive container. Need to improve the quality of handling, especially in space for activities that contribute to the process of autism therapy.In this study, an evaluation of the autism school in Surakarta and surrounding areas and made recommendations for solutions to the existing problems. The method used is qualitative rationalistic with post-occupancy indicative evaluation. Data obtained from field observation of research object, interview with related parties, and literature study. The data obtained is processed by emphasizing the meaning of empiri, understanding and intellectual ability to argue logically with supported empirical data and relevant theory. From the results of these evaluations, prepared spatial planning recommendations based on design criteria that are positively oriented towards increasing autism independence. From the results of the study known that the existing space can be used quite well, although technically inadequate, need improvement in order to function more optimally. The results of this study are expected to be used as a reference for autism school planning in the future.